Predictors of achievement in elementary differential equations - Andres, Virgilio Felipe 1959- (1991)
The predictive abilities of selected intellective and non-intellective factors on the achievement in Elementary Differential Equations were determined in this research. The variables that can best predict the achievement of students in Elementary Differential Equations, students' perceptions on the instructional skills of a mathematics teacher and how this perceptions are related to students' sex and the type of school graduated were also determined.